Ultrasound navigation based on minimally designed vehicle inspired by the bio-sonar strategy of bats. (16th February 2019) - Yamada, Yasufumi; Ito, Kentaro; Tsuji, Takumi; Otani, Kohei; Kobayashi, Ryo; Watanabe, Yoshiaki; Hiryu, Shizuko
ABSTRACT: In this study, we conducted vehicle experiments and a numerical simulation based on a simple algorithm inspired by the bio-sonar system of bats to investigate how the behavioral strategy employed by bats contributes to acoustic navigation for minimal-design sensing. In particular, a double-pulse scanning method inspired from the echolocation behavior of bats was proposed, in which (1) the direction of ultrasound emission by a vehicle equipped with 1 transmitter and 2 receivers was alternately shifted between the movement direction of the vehicle and the direction of the nearest obstacle, and (2) the movement direction of the vehicle was calculated for every double-pulse emission based on integrated information from all echoes detected. As a result of 100 repeated drives in a practical course, the success rate of an obstacle-avoidance drive improved from 13% with the conventional single-pulse scanning method to 73% with the proposed method. Furthermore, the numerical simulation demonstrated that the proposed method achieves robust path planning by suppressing the localization ambiguity due to the interference of multiple echoes. The practical experiments and numerical simulation suggest that bats employ a simple behavioral solution in the operation of acoustic sensing for various problems occurring in the real world. GRAPHICAL ABSTRACT: